Canada–US Relations
XXI, 294 p. 8 illus., 7 illus. in color.
Keywords: This book, the 32nd volume in the Canada Among Nations series, looks to the wide array of foreign policy challenges, choices and priorities that Canada confronts in relations with the US where the line between international and domestic affairs is increasingly blurred. In the context of the Canada-US relationship, this blurring is manifest as a cooperative effort by officials to manage aspects of the relationship in which bilateral institutional cooperation goes on largely unnoticed. Chapters in this volume focus on longstanding issues reflecting some degree of Canada-US coordination, if not integration, such as trade, the environment and energy. Other chapters focus on emerging issues such as drug policies, energy, corruption and immigration within the context of these institutional arrangements. David Carment is Professor of International Affairs at Carleton University, Canada, and Editor of Canadian Foreign Policy Journal. He is Series Editor of Palgrave Macmillan’s Canada and International Affairs. Christopher Sands is Senior Research Professor and Director of the Center for Canadian Studies at Johns Hopkins University’s Paul H. Nitze School of Advanced International Studies in Washington, DC, USA. .